MACROANATOMY OF HIPPOCAMPUS IN BUFFALOES (BUBALUS BUBALIS) - A. Kumaravel; Geetha Ramesh; S. Rajathi; S. Muthukrishnan; V. Ramakrishnan (Indian Journal of Veterinary and Animal Sciences Research, 2024)
The gross studies on the hippocampus were made on 10 specimens each of calves and adults of the Indian buffalo. The hippocampus was a curved elevation, lying immediately ventral to the splenium of the corpus callosum, dorsal to the lateral aspect of the thalamus. It occupied the floor of the inferior horn of the lateral ventricle. The ventricular surface of the hippocampus was covered by a thin layer of white matter, the alveus. Rostrolaterally the alveus joined a thick fibrous band, the hippocampal fimbria which connected the alveus to the fornix. On the ventromedial aspect, a deep groove, the hippocampal sulcus, separated this surface into lateral and medial portions.